Structure and properties of plasma sprayed APS -Ni20Al coatings - Mrdak, Mihailo Rade (Vojnotehnički glasnik / Military Technical Courier, 2013)
The aim of this study is to obtain, by optimizing the deposit parameters, optimal structural and mechanical properties of Ni20Al layers to be applied on a radar station part. The powder was deposited by the process of atmospheric plasma spraying (APS), with a plasma spray (PS) distance of 80, 90 and 100 mm. The coating with the best characteristics was deposited on the hardener of the GTD 2PV8 turbo gas engine for a radar station, in order to reduce the effect of oxidation and vibration on the wear at 450 - 500°C. The quality of Ni20Al coating layers was assessed on the basis of their microstructure, microhardness and tensile strength. The best structure and mechanical properties were found in the layers deposited with a distance of plasma spray of 80 mm. The surfaces morphology of the deposited coatings and the fracture morphology of the best layers were examined with the SEM (scanning electron microscope). The microstructure of the deposited layers of coatings was examined by light microscopy. The microstructural analysis of the deposited layers was performed according to the Pratt-Whitney standard. The evaluation of the mechanical properties of the layers was done by examining microhardness with the HV0.,3 method and tensile testing was used for the bond strength. Studies have shown that the plasma spray distance significantly affects the mechanical properties and the microstructure of coatings. The effect of Ni20Al coating application has been tested on a hardener of the GTD 2PV8 turbo gas engine on a radar station.